Fishing Downstream: Does CSPAP Promotion During PETE Transfer to Teaching Practice by K-12 Physical Educators? - Mulhearn, Shannon C.; Kulinna, Pamela H.; van der Mars, Hans; Stylianou, Michalis; McMullen, Jaimie; Ellison, Douglas (Research quarterly for exercise and sport, 2023)
Physical Education Teacher Education (PETE) training has the potential to influence graduates' decisions as physical educators. Utilizing themes from Rogers' Diffusion of Innovations and Lawson's Occupational Socialization theories, we focused on graduates from a single PETE program which, beginning in 2007, began integrating content, expectations, and experiences relating to an expanded role of the physical educator such as in comprehensive school physical activity programs (CSPAPs). Purpose: The purpose of this study was to examine transfer in terms of university training leading to teaching practices in expanded physical activity programming. Method: An electronic questionnaire was sent to 335 graduates from May 2000 through May 2019. Sixty-seven graduates' questionnaires were investigated looking at perceptions of CSPAP as an innovation, current expanded physical activity (PA) offerings, and memories of PETE. Additionally, 13 participants participated in a school visit and interview which acted as a fidelity check for self-reported levels of expanded PA programming reported in the questionnaire. Results: All 67 graduates included some amount of expanded PA programming. Positive correlations were found with perception of CSPAP as an innovation, for both year of graduation and memory of PETE programming, thus students exposed to CSPAP programming during PETE were implementing components at their schools at higher levels. Conclusion: There is positive potential for professional socialization to influence graduates' practices. Perceptions of CSPAP as an innovation were positive and support the promotion of triability and starting small when PETE programs encourage expanded PA programming.